Triple System Mechanism for Religious Court Summons: Mekanisme Tiga Tingkat untuk Panggilan Pengadilan Agama - W.R. Rido Hakim; Ahmad Syaifudin; Sunardi Sunardi (Indonesian Journal of Innovation Studies, 2026)
General Background Digital transformation in judicial administration has introduced electronic summons (e-summons) as part of the e-Court system in Religious Courts. Specific Background The summons process also requires bailiff summons and registered letters through PT Pos Indonesia because electronic mechanisms cannot accommodate all justice seekers. Knowledge Gap Previous studies have mainly examined e-Court or e-summons implementation, while integrated analysis of e-summons, bailiff summons, and registered letters as a unified mechanism remains limited. Aims This study analyzes the legal regulation and urgency of the Triple System Mechanism for party summons in Religious Court cases. Results Using normative legal research with statutory and conceptual approaches, the study finds that the three mechanisms have complementary legal positions in ensuring valid summons procedures. The integration supports legal certainty, access to justice, and adaptation to diverse community conditions. Novelty This study presents the Triple System Mechanism as an integrated summons model combining electronic, direct, and registered letter procedures. Implications The findings contribute to the development of civil procedural law and electronic judicial administration by providing a conceptual framework for adaptive summons services. Highlights: Three summons procedures operate as complementary mechanisms in judicial administration. Legal regulation accommodates electronic, bailiff, and registered letter procedures. Integrated procedures support access to justice for diverse community conditions. Keywords:Triple System Mechanism, E-Summons, Religious Court, Summoning of the Parties, Legal Certainty